US Indo-Pacific Strategy – Implications for Strategic Stability in South Asia - Bhatti, Nauman Bashir (Journal of Pakistan Administration, 2022)
The “Indo-Pacific Region” is a U.S. political and security construct against China envisaged within the geographical bounds of Pacific and Indian Oceans. The U.S. Indo Pacific Strategy (IPS) details a comprehensive approach along with clear lines of effort and objectives to contain and defeat China in all dimensions – political, strategic, military and economic. While touching upon the genesis of the construct and detailing the geo-political, geo-economic and geo-strategic significance of the region, the paper dilates on the U.S. threat perception that, inter alia, stems from: (i) China’s Belt and Road Initiative (BRI); (ii) Beijing’s growing strategic capabilities and assertive military posturing in South and East China Seas; and (iii) export of China’s governance model that is viewed as a challenge to the established world order. It also reflects on the systematic evolution of the concept in the U.S. legislative frameworks, strategies, policies and approach towards the region since 2017, when China was declared as a “revisionist power” by President Trump’s National Security Strategy. Elaborating on the objectives, contours and implementation methodology of the U.S. IPS, the paper focuses on the Washington’s partnerships pursued under the construct, including enhanced security and defence cooperation. The role of India in the U.S. strategy, growing U.S. – India strategic and defence partnership, and the rapid modernization of Indian conventional and strategic forces, are analyzed in light of existing peace and security situation in South Asia, particularly India’s hostile doctrines and postures against Pakistan. Considering the current state of Pakistan – U.S. relations, Pakistan’s strategic ties with China, implementation of China Pakistan Economic Corridor (CPEC) as part of BRI, and convergence of U.S. – India strategic interests, it has been assessed that U.S. IPS will have significant implications on the Strategic Stability in South Asia and would pose a complex set of challenges for Pakistan which can be categorized under political and diplomatic, regional peace and security, and economic and development dimensions. To offset the implications of U.S. IPS, a set of policy recommendations have been proposed to guide Pakistan’s overall approach to the U.S. construct which is underpinned by national objectives associated with strategic autonomy, long term economic security, peace and stability, and maintaining balance of power in the region.